Correlation between Poly ADP Ribose Polymerase (PARP) expression with Chemotherapy Response in Ovarian Carcinoma - Ria Yuniarti; Wresnindyatsih Wresnindyatsih; Suly Auline Rusminan; Erial Bahar (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2026)
Background Germline mutations in BRCA1 and BRCA2 are high risk factors for ovarian and breast cancer. The risk of ovarian cancer in BRCA1 mutation carriers is 16-68% and 11-30% in BRCA2 mutation carriers.1,2 The enzyme poly ADP ribose polymerase (PARP) plays an important role in DNA damage repair and genome stability and cancer cells change its regulation as a way for tumor cells to survive cell death due to chemotherapeutic agents.3,4 Positive PARP expression is associated with high-grade tumors. advanced stage and is an indicator of aggressive disease. The aim of this study was to examine the relationship between PARP expression and the response to chemotherapy in ovarian carcinoma. Methods A cross sectional study was conducted using 34 samples of paraffin blocks and slides of ovarian carcinoma from oophorectomy and biopsy of patients registered at the Anatomical Pathology Department Faculty of Medicine Sriwijaya University/Dr. Mohammad Hoesin Hospital Palembang for the period January 2019 to December 2021. Each sample was stained by PARP monoclonal antibody. Qualitative interpretation by assessing semi-quantitatively, namely assessing the area/proportion (P) and intensity (I) of the polished, the score is obtained by multiplying the area by the intensity, the results are grouped into 2, score 0-4 was a weak expression, score 6 was a strong expression. Analysis of the relationship between PARP expression and response to chemotherapy was performed using Chi-square test and Spearmann correlation. Results Chi-square test showed that there was a significant relation PARP expression with chemotherapy response, age, CA 125 levels post chemotherapy and stage with p values were 0.008, 0.005, 0.020 dan 0.006 respectively. There was no relation between PARP expression with histopathology subtype with p values was 0.053. Conclusion There is a significant correlation between PARP expression with chemotherapy response, age, CA 125 levels post chemotherapy and stage in ovarian carcinoma